Ballistic impact behavior of thin nickel-base alloy plates at different temperatures - LIU Jiao; ZHENG Bailin; YANG Biao; YU Xiaoqiang; ZHANG Kai; SHI Tongcheng (Journal of Aeronautical Materials, 2019)
To study the aeroengine containment capability in high temperature, experiments and numerical simulations of the spherical nosed projectile impacting thin plate under 25 ℃ and 600 ℃ were performed. Experiments were conducted by using a gas gun. Target plates were impacted by bullets with different initial velocities. The effect of temperature and initial velocity on the deformation, failure pattern and energy absorption of the plate were analyzed. The results show that at higher temperature, the deformation of the target plates is greater, the energy absorbed by the target plates is smaller and the critical ballistic velocities are smaller . The petal deformation of the target plate caused by bending is more obvious under 600 ℃. Numerical simulations of the impact were conducted by using an explicit dynamics FE code (LS-DYNA). The Johnson-Cook material model was used to carry out the analysis. The Johnson-Cook material model parameters were obtained by the separated Hopkinson pressure bar (SHPB) experiment at high temperature. The results obtained from the numerical simulations were compared with those from the experiments. Good correlation is found between experiments and numerical simulations.